Medieval culture and society - Herlihy, David, 1930-1991 (Documentary history of Western civilization., 1968)
Describes the Early Middle Ages, its social order, culture, and literature such as "Beowulf". Also describes the Central Middle Ages, country life and city life, scholasticism, troubadour lyric poetry, and religious literature. Includes the Late Middle Ages with Boccaccio's description of the Black death, Chaucer's picture of medieval society, a sermon by Meister Eckhart, and chapters from "The Imitation of Christ" .